In vitro anticancer, antimicrobial and antiradical properties and bioactive compounds of endemic Wiedemannia orientalis Fisch. & Mey. flowers - Keser, Serhat; Keser, Fatma; Tekin, Suat; Türkoğlu, İsmail; Kaygılı, Omer; Demir, Ersin; Karatepe, Mustafa (Niyazi BULUT, 2022)
W. orientalis is a one-year herbaceous plant, located in the Lamiaceae family, and is called Ballıbaba in Turkish. In the presented study, the antimicrobial and anticancer properties of flowers extracts of endemic W. orientalis were investigated for the first time. Also, it was investigated the antiradical activity and phytochemical contents of this plant extracts. According to our study results, endemic W. orientalis flowers extract show very high anticancer activity against MCF-7, HCT-116 and LNCaP cancer cell lines, high antiradical activity against ABTS radicals, and effective antimicrobial activity against some microorganism caused infection in humans. In conclusion, endemic W. orientalis can be used as an anticancer and antimicrobial agent and this plant can be the subject of further studies in the field of herbal medicine.
Keywords: Chemical Engineering; Kimya Mühendisliği